Implementation of the Tobacco Tactics intervention versus usual care in Trinity Health community hospitals. (December 2016) - Duffy, Sonia; Ronis, David; Ewing, Lee; Waltje, Andrea; Hall, Stephanie; Thomas, Patricia; Olree, Christine; Maguire, Kimberly; Friedman, Lisa; Klotz, Sue; Jordan, Neil; Landstrom, Gay
Abstract Background Guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) implementation framework, a National Institutes of Health-sponsored study compared the nurse-administered Tobacco Tactics intervention to usual care. A prior paper describes theeffectiveness of the Tobacco Tactics intervention. This subsequent paper provides data describing the remaining constructs of the RE-AIM framework. Methods This pragmatic study used a mixed methods, quasi-experimental design in five Michigan community hospitals of which three received the nurse-administered Tobacco Tactics intervention and two received usual care. Nurses and patients were surveyed pre- and post-intervention. Measures includedreach (patient participation rates, characteristics, and receipt of services), adoption (nurse participation rates and characteristics), implementation (pre-to post-training changes in nurses' attitudes, delivery of services, barriers to implementation, opinions about training, documentation of services, and numbers of volunteer follow-up phone calls), andmaintenance (continuation of the intervention once the study ended). Results Reach : Patient participation rates were 71.5 %. Compared to no change in the control sites, there were significant pre- to post-intervention increases in self-reported receipt of print materials in the intervention hospitals (n = 1370, p < 0.001).Adoption : In the intervention hospitals, all targeted units and several non-targeted units participated; 76.0 % (n = 1028) of targeted nurses and 317 additional staff participated in the training, and 92.4 % were extremely or somewhat satisfied with the training.Implementation : Nurses in the intervention hospitals reported increases in providing advice to quit, counseling, medications, handouts, and DVD (allp < 0.05) and reported decreased barriers to implementing smoking cessation services (p < 0.001). Qualitative comments were very positive ("user friendly, " "streamlined, " or "saves time"), although problems with showing patients the DVD and charting in the electronic medical record were noted.Maintenance : Nurses continued to provide the intervention after the study ended. Conclusions Given that nurses represent the largest group of front-line providers, this intervention, which meets Joint Commission guidelines for treating inpatient smokers, has the potential to have a wide reach and to decrease smoking, morbidity, and mortality among inpatient smokers. As we move toward more population-based interventions, the RE-AIM framework is a valuable guide for implementation. Trial registration ClinicalTrials.gov, NCT01309217